The Effect of Religiosity on Juvenile Delinquency in Maulafa Village - Inka Cahyani Soluk; Yenni Damayanti; Juliana M. Y. Benu (Journal of Health and Behavioral Science, 2021)
Adolescence can be said to be a time of strom and stress, so that it make adolescents easily to change, volatile and erratic. Juvenile delinquency is a behavior that includes driving/vehicle, Alcohol, Theft, Cheat, Disturb, Fight, Drugs and media that violate the rules. one of the factors the influence juvenile delinuency is religiosity. The purpose of this study was to determine the effect of religiosity on juvenile delinquency in RT 027 RW 010 Maulafa Village Kecamatan District. The hypothesis in this study is the effect of religiosity on juvenile delinquency in RT 027 RW 010 Maulafa Village Kecamatan District. The research participants were teenagers RT 027 RW 010, Maulafa Village, Kecamatan District. in this study using simple linear regression analysis. The results of this study indicate that product moment correlation of 0,516 is greater than the r table (n=80) at 0,220 with a significaant level of 5%, then H1 is accepted and H0 is rejected so that there is a signifficant effect on variable X and variable Y.